[OP.2D.04] PERIVASCULAR T REGULATORY CELLS AND ENDOTHELIAL DYSFUNCTION IN HUMAN ATHEROSCLEROSIS. (September 2016) - Urbanski, K.; Filip, G.; Filip, M.; Ludew, D.; Szczepaniak, P.; Nosalski, R.; Sagan, A.; Mikolajczyk, T.; Kapelak, B.; Guzik, T.J.
Abstract : Objective: Atherosclerosis is an inflammatory disease associated with an imbalance between pro- and anti-inflammatory mechanisms. While ample evidence is available in animal models, less is known about links between local vascular inflammation in human disease. T regulatory cells (Treg) have been implicated in atherosclerosis in mice but links with human vascular inflammation are poorly understood. Accordingly, we aimed to investigate the relationship between T regs in peripheral blood and locally in perivascular adipose tissue (pVAT) with endothelial function as a key mechanism in pathogenesis of vascular disease. Design and method: Treg (CD3+/CD4+/CD25+/FoxP3+) infiltration was studied in pVAT of atherosclerotic coronary artery (CORO), non-atherosclerotic internal mammary artery (IMA), as well as subcutaneous AT and peripheral blood were quantified using flow cytometry from 50 CABG patients (38 M;12F;age 65y+/-1) with typical atherosclerosis risk factor profile. Vascular function was assessed in IMA segments ex vivo by isometric tension studies of vasorelaxations to acetylcholine and ROS production was measured in vascular segments with 5uM lucigenin enhanced chemiluminescence. Results: Treg infiltration was observed in both IMA and CORO, but was significantly higher in IMA pVAT than in pVAT surrounding CORO (13, 58 ± 15, 6 vs. 4, 74 ± 6, 2 cells/mg; p < 0, 01). Moreover, there was a significant correlation between these two AT depots suggesting systemic pVAT regulation (R = +0, 53; p = 0, 001). Indeed we observed a significant correlation between number of risk factors for atherosclerosis and Treg content (Rs = +0, 33 p = 0, 02). Importantly, there was an inverse correlation between Treg content in peripheral blood and Ach-induced vasorelaxations (R = -0, 31 p < 0, 05). Local T reg infiltration in pVAT was significantly correlated with indices of NO production, as measured by chemiluminescence (R = +0, 58 p = 0, 007). However, NO produced was scavenged by ROS (measured by ratio of L-NAME enhanced/basal superoxide levels) and Treg infiltration in pVAT did not correlate with IMA endothelial function (R = -0.02 p = 0, 92) or total vascular ROS production (R = -0, 12 p = 0, 53). Conclusions: Atherosclerosis is accompanied by local decrease in T regulatory cell content in atherosclerotic vs. non-atherosclerotic arteries, although their amount is linked with classical risk factors for atherosclerosis. Higher peripheral blood T regs are associated with better endothelial function, although it is not achieved through locally infiltrating Tregs.